A voluntary risk information disclosure: a study of Malaysian Public Listed Companies / Rina Fadhilah Ismail, Emmarelda Maswesi Ahmad and Nor Syafinaz Shaffee - Ismail, Rina Fadhilah; Ahmad, Emmarelda Maswesi; Shaffee, Nor Syafinaz (Research Management Institute (RMI), 2017)
The ongoing discussion on the effective risk management practices to facilitate corporate decisions has raised a concern on the usefulness of the reports that focusing on risk and uncertainty in alleviating potential harmful to the companies (Ho & Taylor, 2013). In fact, comprehensive reporting should comprise of both mandatory and voluntary information. This is vital to reduce the information asymmetry between managers and shareholders as well as to evaluate the firm performance by the investors. The need for voluntary information particularly on risks and uncertainties surrounded or impacted the business environment has rising as indicated by Schadewitz and Niskala (2010) that viewed the voluntary disclosure as a tool to differentiate superior and significant information in explaining mandatory information. Eventually, lacking of comprehensive voluntary risk information in annual reports may lead to misinterpretation of current corporate performance condition that will affect the future business operations (Abraham & Cox, 2007; Cabedo & Tirado, 2004). This could place a pressure to the managers to provide sufficient information beyond the mandatory requirements of the capital market in order to facilitate shareholders' investment decisions (Mokhtar & Mellett, 2013). To be exact, managers are encouraged to present a precise, accurate and relevant financial and non-financial information to the investors and regulators. This information is vital in assessing company's performance, risks and uncertainties surrounding or impacting the business environment. During recovery period of the financial crisis, lacking of sufficient risk information may lead to the misinterpretation of current corporate condition that eventually may affect future business operations (Dobler, Lajili, & Zeghal, 2011; Jonas Oliveira, Rodrigues, & Craig, 2011).